Firs-principles investigation of ZrCo and its hydrides. (8th July 2022) - Yang, Youshan; Wang, Lusheng
Abstract: The electronic structures of Zr8 Co8 and its hydrides have been systematically investigated using the first-principles calculation based on density functional theory. Additionally, the influence of the Ti and Hf doping on the atomic bonding properties of Zr8 Co8 and its hydrides (Zr7 HfCo8, Zr7 HfCo8 H, Zr16 Co15 HfH48, Zr7 TiCo8, Zr7 TiCo8 H, and Zr16 Co15 TiH48 compounds) were also studied to provide new insights into the hydrogenation of Zr8 Co8 . The Ti and Hf atoms were occupied the Zr position in the ZrCo alloy, while they were occupied the Co position in the Zr16 Co16 H48 system. Ti and Hf doping could achieve the purpose of anti-disproportionation. Ti and Hf could weak the Zr–Co bond for the improvement of the hydrogenation performance of Zr8 Co8, and the covalence of the Co–H bond was higher than that of the Zr–H bond. The existence of a Co–H covalent bond in the crystal is conducive to the hydrogen absorption of Zr8 Co8 to form Zr16 Co16 H48 . Inhibition of Co–H interaction during Zr8 Co8 hydrogenation can accelerate the formation of Zr8 Co8 H for the improvement of its hydrogenation performance. Highlights: The purpose of this article is to provide new insights into the hydrogenation of Zr8 Co8 . The Ti and Hf occupy the Zr position of ZrCo, while they occupy the Co position of ZrCo hydride. Inhibition of Co–H interaction can improve hydrogenation performance of ZrCo.